Transmembrane serine protease TMPRSS2 activates hepatitis C virus infection. Issue 2 (February 2015) - Esumi, Mariko; Ishibashi, Mariko; Yamaguchi, Hiromi; Nakajima, Satomi; Tai, Yuhi; Kikuta, Sachiko; Sugitani, Masahiko; Takayama, Tadatoshi; Tahara, Maino; Takeda, Makoto; Wakita, Takaji
<x xml:space="preserve">Abstract</x> The human liver reacts to hepatitis C virus (HCV) with a balanced response consisting of host anti‐ and proviral activities. To explore these subtle host responses, we used oligonucleotide microarrays to investigate the differential gene expression between two groups of liver samples with high and low HCV loads (>100‐fold difference). We identified and validated 26 genes that were up‐regulated in livers with high HCV loads, including transmembrane protease serine 2 (TMPRSS2). Trypsin inhibitors inhibited the infection of Huh7‐25‐CD81 cells with cell‐culture–derived HCV (HCVcc) of Japanese fulminant hepatitis 1 isolate at the postbinding and entry step, and trypsin enhanced HCVcc infection at an early stage of infection. Several major transmembrane serine proteases, in particular, furin and hepsin, were detected in Huh7‐25‐CD81 cells, but TMPRSS2 was not. Huh7‐25‐CD81 cell clones stably expressing TMPRSS2‐ WT (wild type) and inactive TMPRSS2‐mutant genes showed positive and negative enhancement of their susceptibility to HCVcc infection, respectively. The enhanced susceptibility of TMPRSS2‐WT Huh7‐25‐CD81 cells was confirmed by knockdown of TMPRSS2 using small interfering RNA. The cell‐surface protease activity of TMPRSS2‐WT cells was markedly active in the cleavage of QAR and QGR, corresponding to amino acid residues at P3 to P1. Conclusion: The cell‐surface activity of a trypsin‐like serine protease, such as TMPRSS2, activates HCV infection at the postbinding and entry stage. Host transmembrane serine proteases may be involved in the sensitivity, persistence, and pathogenesis of HCV infection and be possible targets for antiviral therapy. (Hepatology 2015;61:438‐447)